Assessment of inflammatory markers in Acne vulgaris patients: serum IL-17, IL22, and IL-10 - Al-asadi, Othaim Razzaq Faliyh; Alnasrawi, Taha H; AL-Shemary, Reham. Q (Technium BioChemMed, 2025)
One of the four main factors in the pathophysiology of acne vulgaris (AV) is inflammation, which may be a primary or secondary process caused by Propionibacterium acnes. To counteract inflammatory mediators, the immune system possesses a variety of anti-inflammatory mechanisms. The data supporting the early involvement of the inflammatory pathway in the etiology of AV, a chronic, complex, inflammatory skin condition, has become more clear. This cell line’s activators, Th17 cells, and the cytokines that follow are all probably important in initiating and maintaining the disease. The aim of this study is to determine the degree to which acne vulgaris is influenced by the interleukins IL-10, IL-17, and IL-22. Individualized patients in our study, sex-matched controls were included, and there were 42 male and 58 female AV patients, aged 12 to 30. An enzyme-linked immunosorbent assay (ELISA) was used to measure the serum levels of IL-10, IL-17, and IL-22. The levels were then connected with the severity of acne. In cases, the serum levels of IL-10, IL-17, and IL-22 were 0.34±0.080, 0.13, 0.14±0.0035, 0.136-0.233, and 0.24±0.0142, 0.126-0.243 pg/ml, respectively, while in controls, they were 0.13±0.028, 0.10±0.0085, 0.14±0.0035, 0.117-0.126, and 0.22±0.0089, 0.114-0.127 pg/ml. For IL-10 and IL-17, there was a substantial difference in levels between patients and controls; however, for IL-22, the difference was negligible. The levels of IL-10 and IL-17 showed an extremely strong positive connection. This study came to the conclusion that IL-10 and IL-17 are important effectors in the pathophysiology of AV. In acne lesions, Th17 cells activated by IL-22 are probably the main source of IL-37.